2007
DOI: 10.1177/1352458506072339
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in Pakistan

Abstract: We describe retrospective data from the largest series of patients (n=142) with multiple sclerosis (MS) from Pakistan. Mean age at onset was 27 years, with a female to male ratio of 1.45:1. The disease onset was polysymptomatic in 75% patients. Motor weakness was the most common onset symptom (70%), followed by sensory symptoms (45%). Optico-spinal type of MS was seen in only 3% of patients The course was relapsing-remitting (RR) in 81%, primary progressive (PP) in 21%, and secondary progressive (SP) in 4% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
2
17
0
Order By: Relevance
“…Although their results are inconsistent with reports from Isfahan and Tehran, it is not surprising because the people who live in this area have different ethnicity and lifestyle compared to people in Isfahan and Tehran. The majority of people in Sistan and Baloochestan are from the Baloch ethnic group, which closely resembles the population residing in Pakistan, where MS is reported to be rare [26,27,28]. Furthermore, nearly half of the population still lives in rural areas, while only 17 and 9% of the population of Isfahan and Tehran, respectively, live in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although their results are inconsistent with reports from Isfahan and Tehran, it is not surprising because the people who live in this area have different ethnicity and lifestyle compared to people in Isfahan and Tehran. The majority of people in Sistan and Baloochestan are from the Baloch ethnic group, which closely resembles the population residing in Pakistan, where MS is reported to be rare [26,27,28]. Furthermore, nearly half of the population still lives in rural areas, while only 17 and 9% of the population of Isfahan and Tehran, respectively, live in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the study from Pakistan showed a higher frequency of RIS, despite a lower incidence and prevalence of MS in the region. 23,24,30,31 Gabelic et al 28 showed, in a smaller study in relatives of patients with MS, that 3% fulfilled the RIS criteria by using the DIS-Barkhof criteria, and 10%, with the DIS-Swanton criteria. In healthy volunteers, they found RIS in 2.4% according to the DIS-Barkhof and 3.7% by using DIS-Swanton criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter hospital database from Karachi, Peshawar and Islamabad among 142 MS patients estimated that the mean age at onset was 27 years, with a female to male ratio of 1.45: 1 [63] .…”
Section: Pakistanmentioning
confidence: 99%